PENGARUH CUSTOMER RELATIONSHIP MANAGEMENT (CRM) DAN BRAND IMAGE GUNA MENCIPTAKAN CUSTOMER LOYALTY PADA MOBIL TOYOTA - Salsa Zanedfi (2023)
The automotive industry is one of the fastest growing industries. Toyota is an automotive company with the most sales from year to year. Loyal customers are one of Toyota's keys to success. However, to achieve this, supporters of loyalty are needed, namely customer relationship management and brand image. Therefore, the formulation of the problem that is suitable for this study is determined, namely whether customer relationship management and brand image have an influence on customer loyalty. Then this research was carried out with the aim of proving and analyzing whether there is an influence on customer relationship management and brand image in order to create customer loyalty. The population in this study are consumers who are or have used Toyota cars in DKI Jakarta with quantitative data types and the method used is purposive sampling method. The sample used was 100 respondents. The analysis technique uses Partial Least Square (PLS) using SmartPLS 3.0 software. The results obtained from this study indicate that (1) the customer relationship management variable has a significant positive effect on customer loyalty of 0.486 and (2) the brand image variable has a significant positive effect on customer loyalty of 0.382.